Enhanced superdirectivity of a multi-layered cylinder using a Huygens excitation. (20th October 2020) - Chen, Wan; Fu, Jiahui; Wu, Qun
Abstract: Superdirective antennae with magnetic/electric line source excitation have been studied in the past decade. The realization of superdirectivity suffers from large side-lobes because the form of the excitation of antenna is too simple. In this article, we introduce a technique for increasing the directivity of a superdirective antenna with a complicated excitation source. Huygens source is chosen as the complicated source due to its perfect zero-back-lobe characteristic and is modeled using numerical and analytical methods . A 10-layered cylinder is chosen as the superdirective antenna. Using the Huygens source, the directivity of the multi-layered cylinder was increased by 20% compared to the previous designs and an extremely small back-lobe is obtained. Other proposed designs mainly focus on the optimization of permittivities and permeabilities of the dielectric layers, which is usually time-consuming, while in our approach, the form of the excitation is considered first. Therefore, this method can be adapted for other complicated sources and provides a novel approach for improving the performance of the superdirective antenna.